Will economy get sick when the weather is too hot - Khaw, Darren Zhi Hou; Goh, Bo Wei; Lian, Wei Shien; Tan, Hong Xiu; Tiew, Wei Jian (2020)
The purpose of this research is to determine the impact of climate change towards economic growth in overall, developed and developing countries which total are 166 countries from year 1990 to 2016. This research applies GMM estimator to capture the dynamic effect of data and deal with endogeneity problem. System and Difference GMM apply in this research to run the empirical test. The result shows mixed impact of climate change towards economic growth in overall, developed and developing countries. The major findings for this research show non-linear impact of climate change towards economic growth in overall and developing countries. Meanwhile, the developed countries do not have non-linear impact of climate change towards economic growth.